A compact patch antenna with enhanced bandwidth and efficiency on a fishnet metasurface ground plane in extremely low profile. Issue 11 (11th October 2018) - Wei, Juzheng; Deng, Xiao; Xu, Xiaofei
Abstract: A compact patch antenna is proposed in this work which is designed on a fishnet metasurface ground plane. The impedance bandwidth and radiation efficiency are further enhanced for the proposed meta‐antenna, compared with a conventional one. To verify the design, one proof of the conceptual patch antenna is studied on an optimized metasurface ground plane. Simulated and measured results are in good agreement. Measured results show that the meta‐antenna has a compact patch size as 0.22λ0 × 0.22λ0 . The measured −10 dB impedance bandwidth is 1.74% and the radiation efficiency is 74%. However for the conventional antenna, the patch size is much larger as 0.31λ0 × 0.31λ0. The bandwidth is only 0.73% and the efficiency is 52%. Prominent enhancement of bandwidth and efficiency has been observed for the meta‐antenna while the patch area has reduced nearly 50% compared with those for a conventional antenna. Note the meta‐antenna substrate thickness is only 0.5 mm (0.0036λ0 ), the extremely low profile makes it easy to be integrated with other circuit modules for future portable wireless applications.